Reconstruction of the right anterior circulation with the Pipeline embolization device to achieve treatment of a progressively symptomatic, large carotid aneurysm. (16th September 2009) - Fiorella, D; Albuquerque, F; Gonzalez, F; McDougall, C G; Nelson, P K
Abstract : Introduction: We present the use of the Pipeline embolization device (PED) to achieve reconstruction of the right anterior circulation in a patient with a dolichoectatic internal carotid artery (ICA) and middle cerebral artery (MCA) and an associated symptomatic, large, carotid-ophthalmic segment aneurysm. Clinical presentation: A 36-year-old man presented with progressive right eye vision loss followed by sudden severe headache. Subsequent neuroimaging revealed a large right carotid-ophthalmic segment aneurysm and diffuse ectasia of the supraclinoid ICA and proximal MCA. A coil embolization of the aneurysm was performed without stent support. Over the next year, the patient experienced increasing headache and progressive bitemporal vision loss. Serial MRI showed progressive coil compaction and recanalization of the aneurysm. Treatment: The right anterior circulation was reconstructed with a total of six PEDs that extended from the distal M1 segment of the MCA proximally into the distal cavernous segment of the ICA. Follow-up angiography at 1 and 4 months demonstrated progressive complete occlusion of the aneurysm and a reorganization of blood flow to the anterior cerebral and anterior choroidal arteries. MRI and radiographic imaging provided evidence of progressive contraction of the intra-aneurysmal thrombus. The patient's headaches resolved and serial visual field examinations have demonstrated gradual improvement after treatment. Conclusion: Extensive cerebrovascular reconstructions that are not possible using commercially available endovascular devices can be achieved with Pipeline. The safety, efficacy and long term implications of such reconstructions are currently being defined.